1991
DOI: 10.1159/000186560
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Helicobacter pylori </i>Antibodies in Patients on Chronic Intermittent Haemodialysis

Abstract: The presence of IgG antibodies against Helicobacter pylori in haemodialysis patients was studied. Furthermore the presence of antibodies in different age cohorts was compared with a population of patients suffering from non-ulcer dyspepsia and healthy blood donors. Antibodies were present in 43% of the haemodialysis patients. In the younger age groups the presence was low compared with the control populations; this difference was not present in the older age cohorts. There was an increasing prevalence of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 8 publications
(14 reference statements)
5
20
0
Order By: Relevance
“…A striking feature in the antral biopsies was the absence of the organism in the areas with intestinal metaplasia, even when there was colonization of the adjacent surface epithelium. A similar observation in nonuremic patients has been reported pre viously [27], H. pylori were not seen overlying normal duodenal mucosa or foci of intestinal metaplasia within the stomach [27,28], while they may be seen within the duodenum in association with gastric metaplasia of the mucosa [29,30], Furthermore, in uremic patients Wee et al [21] reported that in all patients in whom H. pylori-like organisms occurred in the duodenal cap, gastric metapla sia was present.…”
Section: Resultssupporting
confidence: 77%
“…A striking feature in the antral biopsies was the absence of the organism in the areas with intestinal metaplasia, even when there was colonization of the adjacent surface epithelium. A similar observation in nonuremic patients has been reported pre viously [27], H. pylori were not seen overlying normal duodenal mucosa or foci of intestinal metaplasia within the stomach [27,28], while they may be seen within the duodenum in association with gastric metaplasia of the mucosa [29,30], Furthermore, in uremic patients Wee et al [21] reported that in all patients in whom H. pylori-like organisms occurred in the duodenal cap, gastric metapla sia was present.…”
Section: Resultssupporting
confidence: 77%
“…The current authors surveyed and summarized the previous studies that studied the prevalence of H. pylori infection in patients receiving hemodialysis (see Table 1). [12,[18][19][20][21][22][23][24][25][26][27][28] In the present study, 40.3% of hemodialysis patients were infected with H. pylori. Considering that the prevalence of H. pylori infection has been reported to be higher than 70% among Japanese adults over 50 years of age, [29] these results indicate the relative percentage of H. pylori-positive hemodialysis patients could be lower than the general patient population.…”
Section: Discussionsupporting
confidence: 47%
“…Previously, it has been reported that there was no difference in the prevalence of H. pylori infection in dialysis patients in regard to age, dialysis period, or the timing of symptom appearance. [32] It has been shown that H. pylori eradication regimens with higher antibiotic dosages provide a higher incidence [18] Netherland No description No description 30 43 Serology Jaspersen D (1995) [19] Germany 127 37 34 20.6 UBT, histology Luzza F (1996) [20] Italy 103 78 103 73 Serology Abu Farsakh NA (1996) [21] Jordan 100 73 92 48.9 Histology…”
Section: Discussionmentioning
confidence: 99%
“…In dialysed patients, the incidence of ulcer is similar to that in patients who do not receive dialysis [5,6]. However, it has been reported that the prevalence of H. pylori infection is lower in dialysed patients [7][8][9]. We investigated the backgrounds of patients receiving dialysis and showing a low prevalence of H. pylori infection.…”
Section: Introductionmentioning
confidence: 96%